Ultrahigh voltage-gradient ZnO-based varistor ceramics via hybrid cold sintering process/spark plasma sintering and post-annealing process - Shenglin Kang; Xuetong Zhao; Qi Wang; Jie Liang; Jing Guo; Xilin Wang; Guilai Yin; Lijun Yang; Ruijin Liao (Journal of Advanced Ceramics)
A high voltage gradient (Vg) of ZnO-based varistor ceramics is critical for realizing miniaturized and lightweight overvoltage protection devices. However, improving Vg of ZnO-based varistor ceramics through conventional high-temperature sintering process remains a significant challenge. Here, we present a strategy to fabricate ultrahigh voltage-gradient ZnO-based varistor ceramics by combining cold sintering process/spark plasma sintering (CSP–SPS) with post-annealing process. Employing CSP–SPS, the ZnO-based varistor ceramics were initially densified at 300 °C and subsequently annealed at a low temperature of 700–900 °C. CSP–SPS technique combined with a low annealing temperature enables the production of ZnO-based varistor ceramics with fine and homogeneous microstructures, while suppressing the volatilization of Bi-rich phases at grain boundaries. This approach achieves the ultrahigh Vg of ~1832.71 V/mm, high nonlinear coefficient (α) of ~106.69, and low leakage current density (JL) of less than 0.2 μA/cm2. This work shows that the integration of CSP–SPS and post-annealing provides a promising way to design ZnO-based varistor ceramics with ultrahigh Vg.